Pullout Capacity of Small-Scale Jack-Like Ground Anchor in Sand with Various Relative Density - Dian Eksana Wibowo; Yusep Muslih Purwana; Bambang Setiawan; Galuh Chrismaningwang (Salehan Institute of Higher Education, 2026)
The pullout behavior of ground anchors in sand is governed by inter-particle friction and mechanical interlocking; however, conventional designs often fail to fully mobilize the surrounding failure zone, resulting in limited uplift capacity. To address this limitation, a jack-like ground anchor was developed, incorporating mechanically expandable wings to increase the soil–anchor contact area and enhance shear resistance. Laboratory pullout tests were conducted in a cylindrical steel tank to investigate the influence of relative density (Dr = 27%, 50%, 80%), embedment depth (H = 0.50–1.00 m), and wing opening angle (0°–75°) on the anchor’s performance. Test results interpreted using the Mazurkiewicz method revealed that increasing wing expansion and soil density substantially improved pullout resistance. In medium-dense sand, capacity increased by up to 250%, and in dense sand, up to 220%, depending on embedment depth. At the deepest embedment and densest condition, capacity increased from 6 kN (closed) to 16 kN (fully opened). These findings confirm that integrating geometric adaptability with soil density optimization significantly enhances uplift efficiency, providing a novel and practical solution for improving anchor performance in granular soils.